Performance of language tasks in patients with ruptured aneurysm of the left hemisphere worses in the post-surgical evaluation - Vieira, Ana Cláudia C; Andrade, Gustavo; Souza, Moysés Ponte de; Griz, Maria de Fátima Leal; Silva, Isabel Eugênia Costa e; Quinino, Saul M. C.; Câmara, Divaldo, Jr; Azevedo-Filho, Hildo R.C (Arquivos de Neuro-Psiquiatria, 2016)
Sub-arachnoid hemorrhage (SAH) promotes impairment of upper cortical functions. However, few information is available emphasizing changes in language after aneurismal SAH and aneurysm location influence. Objective To assess the language and verbal fluency performance in aneurismal SAH pre- and post-surgery in patients caused by an aneurysm of the anterior communicating artery (AcomA), left middle cerebral artery (L-MCA) and left posterior comunicating artery (L-PcomA).Methods Assessment in 79 patients with SAH, on two occasions: pre- and post surgical treatment. They were divided into three groups by the aneurysms’ location.Results Deterioration is detected in the performance of all patients during the post-surgical period; L-MCA aneurysm patients displayed a reduction in verbal naming and fluency; L-PcomA patients deteriorated in the written language and fluency tasks.Conclusion After the surgical procedure the patients decreased in various language tasks and these differences in performance being directly related to the location of the aneurysm.
Keywords: subarachnoid hemorrhage; intracranial aneurysm; language